DNP student mentorship. Issue 7 (July 2020) - Higgins, Karen; Newby, Olivia
Abstract : DNP-prepared NPs are ideal mentors and preceptors for DNP students because they're knowledgeable about DNP educational requirements and have experience as clinicians and healthcare leaders. This article describes a novel mentoring experience with DNP students and leaders of a local NP organization.